Strategic underleveraging and acquisitions - Blomkvist, Magnus; Felixson, Karl; Löflund, Anders; Vyas, Hitesh (Journal of Corporate Finance, 2022)
This paper investigates the Morellec and Zhdanov (2008) (MZ) prediction that firms strategically underleverage to win takeover contests. We document support for several specific MZ model predictions: pre-bid underleveraging increases with bidding competition, synergies offered by targets, investment type, industry concentration, and with firms actively adjusting their capital structure in advance of bidding. An empirically verified financial frictions explanation does not fully account for these patterns. Taken together, we find consistent evidence that strategic underleveraging conditional on the acquisition outlook is an important determinant of capital structure dynamics.